Aberrant regulation of autophagy disturbs fibrotic liver regeneration after partial hepatectomy - Lian, Yuan-E.; Bai, Yan-Nan; Lai, Jian-Lin; Huang, Ai-Min (Frontiers in Cell and Developmental Biology, 2022)
Reports indicate that autophagy is essential for maintaining hepatocyte proliferative capacity during liver regeneration. However, the role of autophagy in fibrotic liver regeneration is incompletely elucidated. We investigated the deregulation of autophagic activities in liver regeneration after partial hepatectomy using a CCl4-induced fibrosis mouse model. The baseline autophagic activity was significantly increased in the fibrotic liver. After 50% partial hepatectomy (PHx), liver regeneration was remarkably decreased, accompanied by increased hepatocyte size and binuclearity ratio. Moreover, the expression of autophagy-related proteins was functionally deregulated and resulted in a reduction in the number of autophagosome and autophagosome–lysosome fusions. We further showed upregulation of autophagy activities through verapamil administration, improved hepatocyte proliferation capacity, and restricted cellular hypertrophy and binuclearity ratio. In conclusion, we demonstrated that the impairment of liver regeneration is associated with aberrant autophagy in fibrotic liver and that enhancing autophagy with verapamil may partially restore the impaired liver regeneration following PHx.